Strategi Kepala Sekolah Dalam Meningkatkan Mutu Pendidikan di Sekolah Nurul Hasaniah - Khotimah, Putri Husnul; Budiama, Budiama; Azzahra, Annisa; Lusianti, Errika Febi; Tammardiyah, Rodia; Putri, Putri (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2024)
One of the elements that can determine the success of an agency or organization is a leader. A leader must be able to manage school administration well so that educational goals are achieved. Leadership in profit and non-profit organizations is a spirit to turn the wheels of empowering the organization. This means that the central role in the organization is never separated from a leader to move the potential that exists within the organization. The shift in the concept of leadership paradigm in this modern age almost equates leadership with power, which can have consequences for the emergence of power malpractice that manifests corruption. As for education, as stated by Edward Sallis that the element of leadership is an important aspect of Total Quality Management in the world of education. Therefore, every leader in an educational institution, be it Elementary School or Madrasah Ibtidaiyah, must really understand their duties and responsibilities well. Leadership in the world of education is one of the things that is very urgent in advancing and improving and improving the achievements of educational institutions. So the key to the success of a school educational institution lies in the concept of complete leadership, complete leadership refers to all school components such as teachers, supervisors and administrators. The principal has an important role in directing as a leader, b ut does not appoint and strengthen the level of leadership integrity. Every educational institution has a different leadership style. Of course, the principal at SD Nurul Hasanah has his own leadership style for managing the Nuruh Hasaniah school in order to improve the quality of education. The research method used is descriptive method with a qualitative approach by directly working to monitor the leadership strategy of Nurul Hasaniah Elementary School. Keywords : Leadership, Strategy, Education, Principal, School.